5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3

Simple and best practice solution for 5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3 equation:


5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3

We simplify the equation to the form, which is simple to understand
5(1.3-6.5x)-6(8.1x-4)=7.1x-12.3

Reorder the terms in parentheses
+(+6.5-32.5x)-6*(8.1x-4)=7.1x-12.3

Remove unnecessary parentheses
+6.5-32.5x-6+*(+8.1x-4+)=+7.1x-12.3

Reorder the terms in parentheses
+6.5-32.5x+(-48.6x+24)=7.1x-12.3

Remove unnecessary parentheses
+6.5-32.5x-48.6x+24=+7.1x-12.3

We move all terms containing x to the left and all other terms to the right.
-32.5x-48.6x-7.1x=-12.3-6.5-24

We simplify left and right side of the equation.
-88.2x=-42.8

We divide both sides of the equation by -88.2 to get x.
x=0.485260770975

See similar equations:

| 5-7x=45-14x | | 5x-4-6x=-10 | | 0.25(8k-4)=k+8-2k | | 8.1a+2.3=5.1a | | 30x+20=30 | | -1.20a=8 | | 8p-2=3p+6 | | -1.2a=8 | | 4x+7=25-2x | | (4x+2)-2(x+1)=12 | | b+6b=-16+3b | | -7+4x=-35 | | 0.72x-19.7=0.3(.2x+18) | | -2x+15=-35 | | -x+1+2x=2 | | 75.00+25x=162.5 | | 3x+27=54 | | 13d-25=3d | | -2c=-16 | | 2x-7=25-2x | | 8ln(11-6x)=4 | | 5x-9-x=7 | | x+5=9x-3 | | xa^2=c-b | | 5x-4+2x=2x+1 | | 6m+16=45x+18-13 | | 1.5h-5=1 | | 4x+31=12x-39 | | ax^2=c-b | | n-n-12=0 | | 11.8-3.4v=6(4.1-v) | | 64+4x=180 |

Equations solver categories